Population‐based analysis of colorectal cancer risk after oophorectomy. Issue 7 (26th April 2016) - Segelman, J.; Lindström, L.; Frisell, J.; Lu, Y.
Abstract: Background: The development of colorectal cancer is influenced by hormonal factors. Oophorectomy alters endogenous levels of sex hormones, but the effect on colorectal cancer risk is unclear. The aim of this cohort study was to examine colorectal cancer risk after oophorectomy for benign indications. Methods: Women who had undergone oophorectomy between 1965 and 2011 were identified from the Swedish Patient Registry. Standard incidence ratios (SIRs) and 95 per cent confidence intervals for colorectal cancer risk were calculated compared with those in the general population. Stratification was carried out for unilateral and bilateral oophorectomy, and hysterectomy without specification of whether the ovaries were removed or not. Associations between the three oophorectomy options and colorectal cancer risk in different locations were assessed by means of hazard ratios (HRs) and 95 per cent confidence intervals calculated by Cox proportional hazards regression modelling. Results: Of 195 973 women who had undergone oophorectomy, 3150 (1·6 per cent) were diagnosed with colorectal cancer at a later date (median follow‐up 18 years). Colorectal cancer risk was increased after oophorectomy compared with that in the general population (SIR 1·30, 95 per cent c.i. 1·26 to 1·35). The risk was lower for younger age at oophorectomy (15–39 years: SIR 1·10, 0·97 to 1·23; 40–49 years: SIR 1·26, 1·19 to 1·33; P for trend < 0·001). The risk was highest 1–4 years after oophorectomy (SIR 1·66, 1·51 to 1·81; P < 0·001). In the multivariable analysis, women who underwent bilateral oophorectomy had a higher risk of rectal cancer than those who had only unilateral oophorectomy (HR 2·28, 95 per cent c.i. 1·33 to 3·91). Conclusion: Colorectal cancer risk is increased after oophorectomy for benign indications. Abstract : Appears increased